ANALISIS IMPLEMENTASI KURIKULUM BERBASIS CINTA DALAM MENGATASI DEGRADASI MORAL SISWA TERHADAP GURU DI SEKOLAH - Affan Najmudin; Khalid Ramdhani; Lau Han Sein (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the phenomenon of students’ moral degradation toward teachers, which is characterized by a decline in respect, the emergence of impolite behavior, and even aggressive actions within the school environment. This issue is not only influenced by internal factors within education but also by external factors such as globalization, the rapid development of technology without proper supervision, and the weakening of character education in both school and family environments. Therefore, an educational approach that addresses the affective and moral dimensions of students is needed.This study aims to analyze the concept and implementation of the love-based curriculum (KBC), examine its impact on students’ moral degradation, and identify the supporting and inhibiting factors in its implementation. The method used is qualitative research with a literature study approach, relying on the analysis of sources such as scientific journals, books, and official documents. The data analysis technique employs the Miles and Huberman model, which includes data reduction, data presentation, and systematic conclusion drawing.The results show that KBC is implemented in an integrated manner within the learning process through dialogic approaches, teacher role modeling, habituation of positive behavior, and the reinforcement of values of love and compassion in learning interactions. The positive impact of KBC implementation is reflected in increased empathy, responsibility, internal discipline, and harmonious emotional relationships between teachers and students. However, its implementation still faces several challenges, such as limited teacher competence, lack of training, and insufficient support from families and the education system. Therefore, the success of KBC requires synergy among schools, teachers, parents, and educational policies to become an effective and sustainable solution in addressing students’ moral degradation.